High-entropy lead-free energy storage ceramic material as well as preparation method and application thereof

By co-doping magnesium-lanthanum-based ceramic materials with high entropy ceramic materials, the preparation process is simplified, and the problem of insufficient energy storage density and efficiency of existing high entropy energy storage ceramic materials is solved, and high energy storage density and efficiency are achieved while reducing preparation cost.

CN119118668AActive Publication Date: 2024-12-13HUBEI UNIV

Patent Information

Application Number
CN202411316132.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-13
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

The existing high-entropy energy storage ceramic materials have shortcomings in energy storage density and energy storage efficiency, and the preparation process is complicated, which increases costs.

Method used

Using (Ca0.2Sr0.2Ba0.2MgxLaxBi0.2-xNa0.2-x)TiO3 high-entropy ceramic material through co-doping of magnesium-lanthanum elements, it is prepared by ball milling, prefiring, molding, glue discharge and sintering, which simplifies the The types of elements and preparation process reduce costs.

Benefits of technology

It has achieved high energy storage density and high energy storage efficiency, with energy storage density reaching 10.1J/cm3, energy storage efficiency reaching 90%, and significantly improved the resistance to voltage breakdown and reduced manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118668A_ABST
    Figure CN119118668A_ABST
Patent Text Reader

Abstract

The invention discloses a high-entropy lead-free energy storage ceramic material and a preparation method and application thereof. The preparation method comprises the following steps: S1, weighing: respectively weighing precursor raw materials according to a stoichiometric ratio for later use; s2, primary ball milling: mixing the weighed precursor raw materials and then carrying out ball milling; s3, pre-sintering: pre-sintering the slurry subjected to ball milling; s4, secondary ball milling: carrying out ball milling on the pre-sintered raw materials again, and drying to obtain pre-sintered ceramic powder; s5, molding: adding a binder into the pre-sintered ceramic powder, and then carrying out compression molding to obtain a ceramic blank; s6, glue discharging and sintering: heating the obtained ceramic green body, and then carrying out heat preservation treatment to obtain a glue-discharged green body; and then, sintering the rubber-removed green body. According to the magnesium-lanthanum co-doped high-entropy ceramic strategy, the relaxation behavior and voltage breakdown resistance of the ceramic material are remarkably improved, the polarization intensity is improved, meanwhile, high energy storage density and high energy storage efficiency are achieved, and the prepared high-entropy ceramic is good in comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of energy storage material preparation, and specifically relates to a high-entropy lead-free energy storage ceramic material and a preparation method and application thereof. Background Art

[0002] With the rapid development of renewable energy, the research and development of energy storage materials has become a focus of social attention and research. Ceramic dielectric materials are insulators that can store energy. When an external electric field is applied to them, the internal charges are enriched on the electrode surface to form a built-in electric field for energy storage. They have outstanding advantages such as ultra-high power density, ultra-fast charge and discharge rate, and no risk of explosion. They have broad application prospects in pulse power systems, hybrid vehicles, microwave communications, electromagnetic catapults, and other fields.

[0003] Compared with traditional low entropy lead-free energy storage ceramic materials (such as (Bi 0.5 Na 0.5 )TiO3, (K, Na)NbO3 and BiFeO3-based ceramics), high entropy ceramics are a type of ceramic material that has five or more elements at a single site and the various elements are randomly and evenly distributed in the lattice. Due to the chaotic arrangement of the radii and valence atoms of different atoms, the long-range orderly arrangement of the ferroelectric is broken, and a series of unique effects such as kinetic hysteresis effect, structural distortion effect, and cocktail effect are produced, which is beneficial to improve its energy storage performance. In the prior art, many researchers have studied high entropy ceramics. For example, patent document CN103288348A provides a high energy storage density barium strontium titanate-based glass ceramic energy storage material and its preparation and application. Through composite modification, while improving the dielectric constant of glass ceramics, it also improves the breakdown field strength, but its energy density is only 2.81J / cm 3 .

[0004] Yuan-Hua Lin's team synthesized Bi with a new pyrochlore structure through high entropy design. 1.5 Zn 0.75 Mg 0.25 Nb 0.75 Ta 0.75 O7 high entropy ceramics have an energy storage efficiency of 91% and an energy storage density of 2.72 J / cm 3 .

[0005] Jiu-Jun Xu team will Bi(Li 0.2 Y 0.2 Mg 0.2 Ti 0.2 Ta 0.2 )O3 high entropy compound is introduced into BaTiO3-(Bi 0.5 Na 0.5)TiO3 matrix, the energy storage density of the ceramic material obtained is 4.89J / cm 3 , the energy storage efficiency is 91.2%. Although the energy storage efficiency of the above high entropy ceramics is high, their energy storage density is generally low.

[0006] In recent years, Professor Chen Jun's team has prepared relaxor ferroelectric ceramics ([(K 0.2 Na 0.8 ) 0.8 Li 0.08 Ba 0.02 Bi 0.1 ](Nb 0.68 Sc 0.02 Hf 0.08 Zr 0.1 Ta 0.08 Sb 0.04 )O3), and obtained 10.06 J / cm 3 The ultra-high recoverable energy density and 90.8% high energy storage efficiency. However, the strategy of simultaneous doping of A and B sites involves a wide variety of elements, which greatly increases the complexity of the material preparation process and the manufacturing cost.

[0007] Therefore, it is still a challenge to develop high entropy energy storage ceramics that have high energy storage density, high energy storage efficiency and low preparation cost. In view of this, the present invention is proposed. Summary of the invention

[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a high-entropy lead-free energy storage ceramic material and a preparation method and application thereof. The obtained ceramic material has the advantages of high energy storage density and high energy storage efficiency, and the preparation method involves fewer types of elements and has great cost advantages.

[0009] In order to achieve the above object, the present invention adopts the following technical solution:

[0010] In a first aspect, the present invention provides a method for preparing a high entropy lead-free energy storage ceramic material, comprising the following steps:

[0011] S1. Weighing: according to the measurement formula (Ca 0.2 Sr 0.2 Ba 0.2 Mg x La x Bi 0.2-x Na 0.2-x )TiO3 respectively weigh the precursor raw materials of calcium salt, strontium salt, barium salt, bismuth salt, sodium salt, titanium salt, magnesium salt and lanthanum salt for use; wherein, 0.02≤x≤0.06

[0012] S2, primary ball milling: mixing the precursor raw materials weighed in step S1 and then ball milling;

[0013] S3, pre-calcining: pre-calcining the slurry after ball milling in step S2;

[0014] S4, secondary ball milling: ball milling the raw material pre-fired in step S3 again, and drying to obtain pre-fired ceramic powder;

[0015] S5: Molding: adding a binder to the pre-fired ceramic powder obtained in step S4, followed by pressing and molding to obtain a ceramic embryo;

[0016] S6, debinding and sintering: the ceramic body obtained in step S5 is heated and then subjected to heat preservation treatment to obtain a debinding green body; the debinding green body is then sintered to obtain a high entropy lead-free energy storage ceramic material.

[0017] As a preferred embodiment of the technical solution of the present invention, in step S1, the precursor raw materials of calcium salt, strontium salt, barium salt, bismuth salt, sodium salt, titanium salt, magnesium salt and lanthanum salt are CaO, SrCO3, BaCO3, Bi2O 3、 Na2CO3, TiO2, MgO, La2O3.

[0018] As a preferred embodiment of the technical solution of the present invention, in step S2, zirconium dioxide ball milling is used for ball milling, and 70-90% of the total mass of the precursor raw materials is added with anhydrous ethanol before ball milling; the ball milling time is 0.5-5h.

[0019] As a preferred embodiment of the technical solution of the present invention, in step S3, the pre-firing temperature is 1100-1200° C., and the pre-firing time is 0.5-5 h.

[0020] As a preferred embodiment of the technical solution of the present invention, in step S4, the secondary ball milling time is 3 to 8 hours.

[0021] As a preferred embodiment of the technical solution of the present invention, in step S5, the pressing pressure is 2 to 4 MPa; and the pressing time is 10 to 20 s.

[0022] As a preferred embodiment of the technical solution of the present invention, in step S6, the insulation treatment temperature is 600-700° C., and the insulation treatment time is 0.5-5 h.

[0023] As a preferred embodiment of the technical solution of the present invention, in step S6, the sintering temperature is 1230-1330° C., and the sintering time is 2-8 hours.

[0024] In a second aspect, the present invention seeks to protect the high entropy lead-free energy storage ceramic material prepared by the above method.

[0025] In a third aspect, the present invention aims to protect the use of the high-entropy lead-free energy storage ceramic material obtained above in energy storage materials in any form.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The high entropy lead-free energy storage ceramic material provided by the present invention preferably has element types and modified doping types, and only by (Ca 0.2 Sr 0.2 Ba 0.2 Bi 0.2 Na 0.2 )TiO3 high entropy ceramics can be co-doped with a small amount of magnesium and lanthanum elements to successfully prepare CSBBNT-xML high entropy energy storage ceramics; the strategy of magnesium and lanthanum co-doping high entropy ceramics, on the one hand, further improves the configuration entropy of the material, resulting in lattice distortion, thereby reducing the size of the nano-ferroelectric domain, thereby significantly increasing the relaxation behavior; on the other hand, it inhibits the growth of grains, increases the number of grain boundaries per unit volume, and increases the volume resistance, thereby significantly improving the material's ability to resist voltage breakdown. Therefore, magnesium and lanthanum co-doping is conducive to achieving both high energy storage density and high energy storage efficiency. Especially when x=0.05, the high entropy ceramics obtained have excellent comprehensive performance, and their energy storage density and efficiency are as high as 10.1J / cm 3 and 90%, and the breakdown voltage is as high as 540kV / cm.

[0028] (2) The high entropy lead-free energy storage ceramic material provided by the present invention has significant economic benefits. Compared with the A and B position high entropy strategies, the present invention adopts the A position high entropy doping strategy, the types of metal elements used are significantly reduced and the magnesium and lanthanum doping content is small, the overall manufacturing cost is significantly reduced, and it has a good prospect for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 XRD pattern of CSBBNT-xML ceramics and a local magnified view of the (200) diffraction peak;

[0030] Figure 2 The natural surface grain morphology of CSBBNT-xML ceramics;

[0031] Figure 3 The relationship curve between density and relative density of CSBBNT-xML ceramics and x;

[0032] Figure 4 is the polarization intensity-polarization electric field curve of CSBBNT-xML ceramics;

[0033] Figure 5 Energy storage density and energy storage efficiency of CSBBNT-xML ceramics. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] In the present invention, a high entropy lead-free energy storage ceramic material is provided, the chemical formula of which is (Ca 0.2 Sr 0.2 Ba 0.2 Mg x La x Bi 0.2-x Na 0.2-x )TiO3 (wherein x=0.02-0.06), abbreviated as CSBBNT-xML, the preparation method thereof comprises the following steps:

[0036] S1. Weighing: Weigh the precursor raw materials of calcium salt, strontium salt, barium salt, bismuth salt, sodium salt, titanium salt, magnesium salt and lanthanum salt respectively according to the stoichiometric ratio and set aside;

[0037] S2, primary ball milling: mixing the precursor raw materials weighed in step S1 and then ball milling;

[0038] S3, pre-calcining: pre-calcining the slurry after ball milling in step S2;

[0039] S4, secondary ball milling: ball milling the raw material pre-fired in step S3 again, and drying to obtain pre-fired ceramic powder;

[0040] S5: Molding: adding a binder to the pre-fired ceramic powder obtained in step S4, followed by pressing and molding to obtain a ceramic embryo;

[0041] S6, debinding and sintering: the ceramic body obtained in step S5 is heated and then subjected to heat preservation treatment to obtain a debinding green body; the debinding green body is then sintered to obtain a high entropy lead-free energy storage ceramic material.

[0042] In the above technical solution, only by (Ca 0.2 Sr 0.2 Ba 0.2 Bi 0.2 Na 0.2 )TiO3 high entropy ceramics were co-doped with a small amount of magnesium and lanthanum elements to successfully prepare high entropy energy storage ceramic materials with both high energy storage density and high energy storage efficiency; and the above-mentioned synthesis strategy also has the advantages of few types of elements and low manufacturing cost.

[0043] In some embodiments, in step S1, the precursor raw materials of the calcium salt, strontium salt, barium salt, bismuth salt, sodium salt, titanium salt, magnesium salt, and lanthanum salt are CaO, SrCO3, BaCO3, Bi2O 3、 Na2CO3, TiO2, MgO, La2O3; the stoichiometric formula is (Ca 0.2 Sr 0.2 Ba 0.2 Mg x La x Bi 0.2-x Na 0.2-x )TiO3 (where x=0.02~0.06).

[0044] In some embodiments, in step S2, the ball milling is performed by a zirconium dioxide ball mill, and 70-90% of the total mass of each precursor raw material is added with anhydrous ethanol before the ball milling; the ball milling time is 0.5-5 hours. Preferably, the amount of anhydrous ethanol added is 80% of the total mass of each precursor raw material, and the ball milling time is 2 hours.

[0045] In some embodiments, in step S3, the pre-burning temperature is 1100-1200°C, and the pre-burning time is 0.5-5h. It is understandable that the pre-burning temperature can be a value among 1100°C, 1110°C, 1120°C, 1130°C, 1140°C, 1150°C, 1160°C, 1170°C, 1180°C, 1190°C, 1200°C, or any value within the above range; similarly, the pre-burning time can be a value among 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, or any value within the above range.

[0046] In some embodiments, in step S4, the secondary ball milling time is 3 to 8 hours. The ball milling also uses a zirconium dioxide ball mill, and the ball milling time can be a value among 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours or any value within the above range. Preferably, the ball milling time is 4 hours. The drying temperature is preferably 80°C.

[0047] In some embodiments, in step S5, the pressing pressure is 2-4 MPa; the pressing time is 10-20 s. It is understood that the pressing pressure can be 2 MPa, 2.1 MPa, 2.2 MPa, 2.3 MPa, 2.4 MPa, 2.5 MPa, 2.6 MPa, 2.7 MPa, 2.8 MPa, 2.9 MPa, 3 MPa, 3.1 MPa, 3.2 MPa, 3.3 MPa, 3.4 MPa, 3.5 MPa, 3.6 MPa, 3.7 MPa, 3.8 MPa, 3.9 MPa, 4 MPa or any value within the above range; the pressing time can be 10 s, 11 s, 12 s, 13 s, 14 s, 15 s, 16 s, 17 s, 18 s, 19 s, 20 s or any value within the above range. Preferably, the pressing pressure is 3 MPa; the pressing time is 15 s.

[0048] In some embodiments, in step S6, the heat preservation treatment temperature is 600-700°C, and the heat preservation treatment time is 0.5-5h. It is understandable that the heat preservation treatment temperature can be a value among 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, or any value within the above range; the heat preservation treatment time is a value among 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, or any value within the above range. Preferably, the heat preservation treatment temperature is 650°C, and the heat preservation treatment time is 1h.

[0049] In some embodiments, in step S6, the sintering temperature is 1230-1330°C, and the sintering time is 2-8h. It is understandable that the sintering temperature can be a value among 1230°C, 1240°C, 1250°C, 1260°C, 1270°C, 1280°C, 1290°C, 1300°C, 1310°C, 1320°C, 1330°C, or any value within the above range; the sintering time can be a value among 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, or any value within the above range.

[0050] Next, the technical solution of the present invention is further described with specific embodiments.

[0051] Example 1

[0052] A method for preparing a high entropy lead-free energy storage ceramic material comprises the following steps:

[0053] (1) Weighing: According to the stoichiometric ratio of each component in the chemical formula (CSBBNT-0.02ML), weigh the metal precursor compound raw materials, including CaO, SrCO3, BaCO3, Bi2O3, Na2CO3, TiO2, MgO, and La2O3;

[0054] (2) Primary ball milling: The weighed precursor material and zirconium dioxide ball milling beads were placed in a ball milling jar, and 80% of the total weight of the drug was added with anhydrous ethanol for ball milling. The speed was increased to 50, 100, 150, 200 and finally 250 r / min every 5 minutes, and finally the ball milling was carried out at a speed of 250 r / min for 2 h;

[0055] (3) Pre-calcination: The ground slurry is placed in a constant temperature drying oven at 80°C to completely evaporate the alcohol in the drug, then placed in a crucible and transferred to a muffle furnace for pre-calcination at a temperature of 1100°C for 3 hours.

[0056] (4) Secondary ball milling: The pre-fired powder is mixed with anhydrous ethanol and ball milled for 4 h, and the ball-milled slurry is dried at 80 °C to obtain the final pre-fired ceramic powder;

[0057] (5) Molding: Add an appropriate amount of 8 wt % polyvinyl alcohol ethanol solution as a binder to an appropriate amount of pre-fired ceramic powder and mix them evenly. Fill the mold with the mixed powder and press it into shape using a tablet press. The applied pressure is 3 MPa and the pressure is kept constant for 15 seconds to obtain a ceramic green disc with a flat and fine surface and no internal stratification. The diameter is about 8 mm and the thickness is about 0.9 mm.

[0058] (6) Debinding and sintering: The pressed ceramic body is placed in a muffle furnace and heated to 650°C and kept warm for 1 hour for debinding. The debinded green body is placed in a muffle furnace for sintering at a sintering temperature of 1230°C and a sintering holding time of 4 hours, and finally a high entropy ceramic with a magnesium-lanthanum co-doping amount of 2% is obtained.

[0059] Example 2

[0060] A method for preparing a high entropy lead-free energy storage ceramic material comprises the following steps:

[0061] (1) Weighing: According to the stoichiometric ratio of each component in the chemical formula (CSBBNT-0.03ML), weigh the metal precursor compound raw materials, including CaO, SrCO3, BaCO3, Bi2O3, Na2CO3, TiO2, MgO, and La2O3;

[0062] (2) Primary ball milling: The weighed precursor material and zirconium dioxide ball milling beads were placed in a ball milling jar, and 80% of the total weight of the drug was added with anhydrous ethanol for ball milling. The speed was increased to 50, 100, 150, 200 and finally 250 r / min every 5 minutes, and finally the ball milling was carried out at a speed of 250 r / min for 2 h;

[0063] (3) Pre-calcination: The ground slurry is placed in a constant temperature drying oven at 80°C to completely evaporate the alcohol in the drug, then placed in a crucible and transferred to a muffle furnace for pre-calcination at a temperature of 1100°C for 3 hours.

[0064] (4) Secondary ball milling: The pre-fired powder is mixed with anhydrous ethanol and ball milled for 4 h, and the ball-milled slurry is dried at 80 °C to obtain the final pre-fired ceramic powder;

[0065] (5) Molding: Add an appropriate amount of 8 wt % polyvinyl alcohol ethanol solution as a binder to an appropriate amount of pre-fired ceramic powder and mix them evenly. Fill the mold with the mixed powder and press it into shape using a tablet press. The applied pressure is 3 MPa and the pressure is kept constant for 15 seconds to obtain a ceramic green disc with a flat and fine surface and no internal stratification. The diameter is about 8 mm and the thickness is about 0.9 mm.

[0066] (6) Debinding and sintering: The pressed ceramic body is placed in a muffle furnace and heated to 650°C and kept warm for 1 hour for debinding. The debinded green body is placed in a muffle furnace for sintering at a sintering temperature of 1230°C and a sintering holding time of 4 hours, and finally a high entropy ceramic with a magnesium-lanthanum co-doping amount of 3% is obtained.

[0067] Example 3

[0068] A method for preparing a high entropy lead-free energy storage ceramic material comprises the following steps:

[0069] (1) Weighing: According to the stoichiometric ratio of each component in the chemical formula (CSBBNT-0.04ML), weigh the metal precursor compound raw materials, including CaO, SrCO3, BaCO3, Bi2O3, Na2CO3, TiO2, MgO, and La2O3;

[0070] (2) Primary ball milling: The weighed precursor material and zirconium dioxide ball milling beads were placed in a ball milling jar, and 80% of the total weight of the drug was added with anhydrous ethanol for ball milling. The speed was increased to 50, 100, 150, 200 and finally 250 r / min every 5 minutes, and finally the ball milling was carried out at a speed of 250 r / min for 2 h;

[0071] (3) Pre-calcination: The ground slurry is placed in a constant temperature drying oven at 80°C to completely evaporate the alcohol in the drug, then placed in a crucible and transferred to a muffle furnace for pre-calcination at a temperature of 1150°C for 3 hours.

[0072] (4) Secondary ball milling: The pre-fired powder is mixed with anhydrous ethanol and ball milled for 4 h, and the ball-milled slurry is dried at 80 °C to obtain the final pre-fired ceramic powder;

[0073] (5) Molding: Add an appropriate amount of 8 wt % polyvinyl alcohol ethanol solution as a binder to an appropriate amount of pre-fired ceramic powder and mix them evenly. Fill the mold with the mixed powder and press it into shape using a tablet press. The applied pressure is 3 MPa and the pressure is kept constant for 15 seconds to obtain a ceramic green disc with a flat and fine surface and no internal stratification. The diameter is about 8 mm and the thickness is about 0.9 mm.

[0074] (6) Debinding and sintering: The pressed ceramic body is placed in a muffle furnace and heated to 650°C and kept warm for 1 hour for debinding. The debinded green body is placed in a muffle furnace for sintering at a sintering temperature of 1280°C and a sintering holding time of 4 hours, and finally a high entropy ceramic with a magnesium-lanthanum co-doping amount of 4% is obtained.

[0075] Example 4

[0076] A method for preparing a high entropy lead-free energy storage ceramic material comprises the following steps:

[0077] (1) Weighing: According to the stoichiometric ratio of each component in the chemical formula (CSBBNT-0.05ML), weigh the metal precursor compound raw materials, including CaO, SrCO3, BaCO3, Bi2O3, Na2CO3, TiO2, MgO, and La2O3;

[0078] (2) Primary ball milling: The weighed precursor material and zirconium dioxide ball milling beads were placed in a ball milling jar, and 80% of the total weight of the drug was added with anhydrous ethanol for ball milling. The speed was increased to 50, 100, 150, 200 and finally 250 r / min every 5 minutes, and finally the ball milling was carried out at a speed of 250 r / min for 2 h;

[0079] (3) Pre-calcination: The ground slurry is placed in a constant temperature drying oven at 80°C to completely evaporate the alcohol in the drug, then placed in a crucible and transferred to a muffle furnace for pre-calcination at a temperature of 1150°C for 3 hours.

[0080] (4) Secondary ball milling: The pre-fired powder is mixed with anhydrous ethanol and ball milled for 4 h, and the ball-milled slurry is dried at 80 °C to obtain the final pre-fired ceramic powder;

[0081] (5) Molding: Add an appropriate amount of 8 wt % polyvinyl alcohol ethanol solution as a binder to an appropriate amount of pre-fired ceramic powder and mix them evenly. Fill the mold with the mixed powder and press it into shape using a tablet press. The applied pressure is 3 MPa and the pressure is kept constant for 15 seconds to obtain a ceramic green disc with a flat and fine surface and no internal stratification. The diameter is about 8 mm and the thickness is about 0.9 mm.

[0082] (6) Debinding and sintering: The pressed ceramic body is placed in a muffle furnace and heated to 650°C and kept warm for 1 hour for debinding. The debinded green body is placed in a muffle furnace for sintering at a sintering temperature of 1280°C and a sintering holding time of 4 hours, and finally a high entropy ceramic with a magnesium-lanthanum co-doping amount of 5% is obtained.

[0083] Example 5

[0084] A method for preparing a high entropy lead-free energy storage ceramic material comprises the following steps:

[0085] (1) Weighing: According to the stoichiometric ratio of each component in the chemical formula (CSBBNT-0.06ML), weigh the metal precursor compound raw materials, including CaO, SrCO3, BaCO3, Bi2O3, Na2CO3, TiO2, MgO, and La2O3;

[0086] (2) Primary ball milling: The weighed precursor material and zirconium dioxide ball milling beads were placed in a ball milling jar, and 80% of the total weight of the drug was added with anhydrous ethanol for ball milling. The speed was increased to 50, 100, 150, 200 and finally 250 r / min every 5 minutes, and finally the ball milling was carried out at a speed of 250 r / min for 2 h;

[0087] (3) Pre-burning: The ground slurry is placed in a constant temperature drying oven at 80°C to completely evaporate the alcohol in the drug, then placed in a crucible and transferred to a muffle furnace for pre-burning at a temperature of 1200°C for 3 hours.

[0088] (4) Secondary ball milling: The pre-fired powder is mixed with anhydrous ethanol and ball milled for 4 h, and the ball-milled slurry is dried at 80 °C to obtain the final pre-fired ceramic powder;

[0089] (5) Molding: Add an appropriate amount of 8 wt % polyvinyl alcohol ethanol solution as a binder to an appropriate amount of pre-fired ceramic powder and mix them evenly. Fill the mold with the mixed powder and press it into shape using a tablet press. The applied pressure is 3 MPa and the pressure is kept constant for 15 seconds to obtain a ceramic green disc with a flat and fine surface and no internal stratification. The diameter is about 8 mm and the thickness is about 0.9 mm.

[0090] (6) Debinding and sintering: The pressed ceramic body is placed in a muffle furnace and heated to 650°C and kept warm for 1 hour for debinding. The debinded green body is placed in a muffle furnace for sintering at a sintering temperature of 1330°C and a sintering holding time of 4 hours, and finally a high entropy ceramic with a magnesium-lanthanum co-doping amount of 6% is obtained.

[0091] Comparative Example 1

[0092] A method for preparing a high entropy lead-free energy storage ceramic material comprises the following steps:

[0093] (1) Weighing: According to the stoichiometric ratio of each component in the chemical formula (CSBBNT-0ML), weigh the metal precursor compound raw materials, including CaO, SrCO3, BaCO3, Bi2O3, Na2CO3, and TiO2;

[0094] (2) Primary ball milling: The weighed precursor material and zirconium dioxide ball milling beads were placed in a ball milling jar, and 80% of the total weight of the drug was added with anhydrous ethanol for ball milling. The speed was increased to 50, 100, 150, 200 and finally 250 r / min every 5 minutes, and finally the ball milling was carried out at a speed of 250 r / min for 2 h;

[0095] (3) Pre-calcination: The ground slurry is placed in a constant temperature drying oven at 80°C to completely evaporate the alcohol in the drug, then placed in a crucible and transferred to a muffle furnace for pre-calcination at a temperature of 1100°C for 3 hours.

[0096] (4) Secondary ball milling: The pre-fired powder is mixed with anhydrous ethanol and ball milled for 4 h, and the ball-milled slurry is dried at 80 °C to obtain the final pre-fired ceramic powder;

[0097] (5) Molding: Add an appropriate amount of 8 wt % polyvinyl alcohol ethanol solution as a binder to an appropriate amount of pre-fired ceramic powder and mix them evenly. Fill the mold with the mixed powder and press it into shape using a tablet press. The applied pressure is 3 MPa and the pressure is kept constant for 15 seconds to obtain a ceramic green disc with a flat and fine surface and no internal stratification. The diameter is about 8 mm and the thickness is about 0.9 mm.

[0098] (6) Debinding and sintering: The pressed ceramic body is placed in a muffle furnace and heated to 650°C and kept warm for 1 hour for debinding. The debinded green body is placed in a muffle furnace for sintering at a sintering temperature of 1230°C and a sintering holding time of 4 hours to finally obtain a high entropy ceramic without magnesium and lanthanum doping.

[0099] The performance of the ceramic materials prepared in each embodiment and comparative example was tested. Figure 1 to Figure 5 .

[0100] from Figure 1It can be seen that all ceramics have a single perovskite structure, indicating that Mg and La elements are completely dissolved in the CSBBNT-xML ceramic lattice. According to the local magnification of the (200) diffraction peak, it can be seen that there is no splitting phenomenon in the diffraction peak, and the diffraction peak has good symmetry, indicating that all ceramics have a long-range pseudo-cubic structure. As x increases, the (200) diffraction peak gradually moves to the low angle direction, indicating that the introduction of Mg and La causes the unit cell to expand.

[0101] from Figure 2 In the figure, we can see the natural surface SEM images of CSBBNT-xML ceramics. All ceramics have a dense microstructure, with the grains tightly bound together and no obvious large pores, indicating that the samples have good sintering quality. Moreover, as x increases, the grain size gradually decreases.

[0102] from Figure 3 It can be seen that with the increase of x, the ceramic density gradually decreases, while the relative density always remains at a high level, all above 95%.

[0103] from Figure 4 It can be seen that for the ceramic sample with x = 0, about 62 μC / cm is obtained under an electric field of 300 kV / cm. 2 The ultra-high polarization strength is 8μC / cm 2 It has a lower residual polarization intensity of about 100 kV / cm, but due to the rapid polarization saturation, its polarization value changes from linear to parabolic growth at an electric field of about 100 kV / cm, resulting in a high maximum polarization value, but a small area enclosed by the Y axis, and a low calculated recoverable energy density. In addition, the lower maximum breakdown strength also leads to a low energy storage density. As x increases, the polarization value under the same electric field becomes lower and lower, but the breakdown field strength first increases and then decreases. When x = 0.05, the breakdown electric field is as high as 540 kV / cm, and the maximum polarization intensity is 53 μC / cm 2 , with the best energy density and energy storage efficiency.

[0104] from Figure 5 It can be seen that as x increases, the energy storage density of the sample increases first and then decreases. When x = 0.05, the maximum energy density is 10.1 J / cm 3 , and the energy storage efficiency is as high as 90%.

[0105] The present invention illustrates the technical concept of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of individual raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a high entropy lead-free energy storage ceramic material, It is characterized in that The steps include: S1. Weighing: according to the measurement formula (Ca 0.2 Sr 0.2 Ba 0.2 Mg x La x Bi 0.2-x Na 0.2-x )TiO 3 Weigh the precursor raw materials of calcium salt, strontium salt, barium salt, bismuth salt, sodium salt, titanium salt, magnesium salt and lanthanum salt respectively and set aside; wherein, 0.02≤x≤0.06; S2, primary ball milling: mixing the precursor raw materials weighed in step S1 and then ball milling; S3, pre-calcining: pre-calcining the slurry after ball milling in step S2; S4, secondary ball milling: ball milling the raw material pre-fired in step S3 again, and drying to obtain pre-fired ceramic powder; S5: Molding: adding a binder to the pre-fired ceramic powder obtained in step S4, followed by pressing and molding to obtain a ceramic embryo; S6, debinding and sintering: the ceramic body obtained in step S5 is heated and then subjected to heat preservation treatment to obtain a debinding green body; the debinding green body is then sintered to obtain a high entropy lead-free energy storage ceramic material.

2. A method for preparing a high entropy lead-free energy storage ceramic material according to claim 1, It is characterized in that In step S1, the precursor raw materials of calcium salt, strontium salt, barium salt, bismuth salt, sodium salt, titanium salt, magnesium salt and lanthanum salt are CaO, SrCO 3 、BaCO 3 、Bi 2 O 3、 Na 2 CO 3 、TiO 2 、MgO、La 2 O 3 .

3. A method for preparing a high entropy lead-free energy storage ceramic material according to claim 1, It is characterized in that In step S2, zirconium dioxide ball milling is used for ball milling, and 70-90% of the total mass of the precursor raw materials is added with anhydrous ethanol before ball milling; the ball milling time is 0.5-5h.

4. A method for preparing a high entropy lead-free energy storage ceramic material according to claim 1, It is characterized in that In step S3, the pre-firing temperature is 1100-1200° C., and the pre-firing time is 0.5-5 h.

5. A method for preparing a high entropy lead-free energy storage ceramic material according to claim 1, It is characterized in that In step S4, the secondary ball milling time is 3 to 8 hours.

6. A method for preparing a high entropy lead-free energy storage ceramic material according to claim 1, It is characterized in that In step S5, the pressing pressure is 2-4 MPa, and the pressing time is 10-20 s.

7. The method for preparing a high entropy lead-free energy storage ceramic material according to claim 1, It is characterized in that In step S6, the heat preservation treatment temperature is 600-700° C., and the heat preservation treatment time is 0.5-5 h.

8. The method for preparing a high entropy lead-free energy storage ceramic material according to claim 1, It is characterized in that In step S6, the sintering temperature is 1230-1330° C., and the sintering time is 2-8 hours.

9. A high entropy lead-free energy storage ceramic material prepared by the method according to any one of claims 1 to 8.

10. Use of the high entropy lead-free energy storage ceramic material according to claim 9 in the preparation of energy storage materials.

Citation Information

Patent Citations

  • High-energy-density barium strontium titanate based glass ceramic energy storage material as well as preparation and application thereof

    CN103288348A

  • Temperature-sensitive ceramic material with high temperature coefficient and preparation method thereof

    CN109206135A

  • Method for preparing high-entropy ceramic based on flash burning variable current and high-entropy ceramic

    CN118405919A

  • Preparation of solid standard sample for analysis

    JP1993005680A

  • Low temperature co-fired ceramic material and preparation method therefor

    US20160264470A1

Cited By

  • High-entropy anti-ferroelectric ceramic material with high energy storage performance as well as preparation method and application of high-entropy anti-ferroelectric ceramic material

    CN119775004A

  • High-entropy antiferroelectric ceramic material with high energy storage performance and preparation method and application thereof

    CN119775004B

  • Lead-free energy storage ceramic material with excellent fatigue resistance as well as preparation method and application of lead-free energy storage ceramic material

    CN120208670A